Blockchain and trade: Not a fix for Brexit, but could revolutionise global value chains (if governments let it) - Nicolas Botton (European Centre for International Political Economy (ECIPE), 2018)
One of the most tone-deaf suggestions in the Brexit proceedings so far came in August 2017, when the UK Brexit team released a long-awaited position paper setting out its proposal on how to manage its border with Ireland. It suggested that "technology-based solutions" - meaning blockchain, the technology behind cryptocurrencies such as Bitcoin - could be implemented to "make it easier to comply with customs procedures." The UK's vague and misguided solution was quickly ridiculed by experts at home, as well as seasoned counterparts abroad. Although blockchain technology has now been around for ten years, it has not seen any meaningful implementation in global supply-chains, let alone within customs offices. Indeed, a "seamless and frictionless" border in compliance with fundamental customs procedures - itself a unicorn - cannot simply be coded into existence on its own. In reality, questions of capacity and time constraints mean that technological solutions are actually unworkable ...
Keywords: 330